Comparison of the Nasab of Adulterous Children According to Al-Qurthubi and Wahbah Zuhaili - Mashluhah , Mita Emil; Mahmud, Amir; Rohtih, Wiwin Ainis; Kuswoyo , Nyoko Adi (Literacy: Journal of Education and Social Science, 2024)
Nasab determines the part of inheritance, guardianship, nurturing, nurturing and things related to it. Without a nasab relationship, many things will be difficult to solve. Children resulting from adultery are considered legally invalid because adultery is considered an act that is not halal and violates the provisions of sharia. In this case, the child does not have the legal nasab of his biological father if sufficient evidence shows that the child is the result of adultery. In Islam, a child born from an extramarital relationship is considered not to have a nasab (lineage) relationship with his biological father, but only with his mother. Therefore, there are two differences of opinion of mufassir about the nasab of adultery children The purpose of this study is to find out how different opinions are about the nasab of adultery children according to Al-Qurthubu and Wahbah Zuhaili. This study uses a comparative research method with a qualitative approach, namely by looking for differences contained in various primary and secondary sources and exploring and describing the research with a description of differences of opinion about the nasab of the child of adultery Imam Al-Qurthubi argues about the fate of the child of adultery that the child born from the result of adultery does not follow his father but follows his mother, If the child is born to a woman, then he cannot be the guardian in his marriage and can be married by the husband of the mother. According to Wahbah Zuhaili, children born from adultery are haram to marry a man from the mother because the man is still included in the category of mushoharoh. Marriage of a pregnant woman because adultery is allowed. If she gives birth to a child after six months of the marriage contract, her destiny will be to that man. If it is less than six months from the time of the marriage contract, then it is not given to him unless the man makes a vow that the child is his child and does not explain that the child is not from adultery.